the Tree of Life as a Research Methodology - Estrada, Vivian M. Jiménez (The Australian Journal of Indigenous Education, 2005)
Abstract This paper is grounded on the premise that research, as a colonising practice, needs constant reconceptualisation and rethinking. I propose a methodology based on some of the values, visions and stories from my own Maya Indigenous culture and knowledge in addition to other Indigenous cultures across the world. I argue that researchers need to constantly acknowledge and change the negative impacts of ignoring multiple ways of knowing by engaging in respectful methods of knowledge collection and production. This paper contributes to the work Indigenous scholars have done in the area of research methodologies and knowledge production. First, a general overview of the values and concepts embedded in the Ceibaor the “Tree of Life” is presented; then, a discussion of what respectful research practices entail follows; finally, it concludes with a reflection on how the Ceibais a small example of how researchers can adapt their research methodology to the local context.